Mengetahui Tanggapan Publik Terhadap Inisiatif Sosial Perusahaan - Khairunnisa Nurul Azizah (Jurnal Ilmu Komunikasi Acta Diurna, 2021)
The Corporate Social Initiatives (CSI) is an essential component in increasing public acceptance of the company. Previous research has shown that corporate social marketing is the most effective type of corporate social initiative in influencing the company's image in the public's eyes. Social media is one of the new communication channel options to socialize the company's social initiatives to the public due to the high number of social media users in Indonesia. This study explores how corporate social initiatives and message content affect public responses to posts on social media specifically for corporate social responsibility from Pertamina, namely the Pertamina Foundation.